In situ expression of mononuclear cell markers and interleukin-2 receptor in renal allograft biopsies of acute rejection and borderline cases - Rodrigues, Fernanda M. D. [UNESP]; De Carvalho, Maria Fernanda C. [UNESP]; Franchi, Marcos R. [UNESP]; Gandin, Celene M. C. [UNESP]; Viero, Rosa Marlene [UNESP] (Taylor & Francis, 2007)
The correct diagnosis of renal allograft rejection may be difficult using only clinical and/or histopathological criteria. Immunological assays should be considered in order to evaluate the phenotype of inflammatory infiltrate in renal allograft biopsies. Immunohistochemical studies were performed to detect mononuclear cells, CD4 and CD8 T lymphocytes, B lymphocytes, macrophages, null cells, and positive cells for interleukin-2 receptors. A total of 41 allograft biopsies classified into three groups were studied: acute cellular rejection (28 biopsies/22 patients), borderline (7 biopsies/5 patients) and control (6 biopsies/6 patients). In the rejection group (RG), increased cellularity was found mainly at the tubulo-interstitial level. Expression of CD8 positive cells was higher in RG when compared to borderline (BG) and control (CG) groups, respectively (0.9 vs. 0.0 vs. 0.35 cells/mm2; p < 0.001). Expression of macrophages was not statistically significant among the three groups (RG = 0.6 vs. BG = 0.2 vs. CG = 0.0 cells/mm2; p < 0.02). In the BG, CD4 + cells predominated (BG = 0.2 vs. RG = 0.05 vs. CG = 0.0 cells/mm2; p < 0.05). Clinically these patients were treated as cases of acute rejection. The numbers and different types of infiltrating cells did not correlate with patient's clinical outcome. Copyright © Informa Healthcare.
Keywords: Cells typing; Morphometry; Rejection; Renal allograft; cell marker; interleukin 2 receptor; adolescent; adult; aged; B lymphocyte; biopsy; CD4+ T lymphocyte; CD8+ T lymphocyte; cell count; cell infiltration; cell type; clinical article; controlled study; female; human; human tissue; immunohistochemistry; kidney allograft; kidney graft rejection; macrophage; male; mononuclear cell; null cell; outcome assessment; priority journal; statistical significance; Adolescent; Adult; Antigens, CD; Biological Markers; Biopsy; Female; Graft Rejection; Humans; Kidney; Kidney Transplantation; Leukocytes, Mononuclear; Male; Middle Aged; Phenotype; Receptors, Interleukin-2